Fatigue Initiation Fail Mode Classifiation of a Nickel-base Superalloy - Forsman, Stefan (My University, 2012)
Inconel-718 is a nickel-base superalloy frequently used in aircraft engines and land-based turbines for its high-temperature and corrosion resistance. In this work a large number of fracture surfaces from fatigue specimens of Inconel-718 have been studied with the main purpose to identify and learn more of initiation mechanisms acting in this specific alloy. Initiation sites have been identified, measured by size and investigated using SEM in an attempt to determine the cause of crack initiation. Specifically the impact of casting defects was of interest. It has been found that facets are the primary initiation points for cracks at RT and 650 C and not large defects such as pores or inclusions, two internal initiations found was connected to embrittlement through laves phase. Surface initiations are in the size range of 40-170 m, this size was approximated to a good degree by Kitagawa-Takahashi diagrams that gave an average maximum defect size of 190 m.
Keywords: Fysik; Physical Sciences